The application of the scratching technique has the same effect on Pleurotus spp.? - Vieira, Wagner Gonçalves [UNESP]; Alberti, María Melisa; Pardo-Giménez, Arturo; Iossi, Matheus Rodrigo [UNESP]; Dias, Eustáquio Souza; Zied, Diego Cunha [UNESP] (FapUNIFESP (SciELO), 2023)
The present work evaluated the agronomic behavior of species and varieties of Pleurotus submitted or not to the scratching technique. The cultivated species/varieties were Pleurotus ostreatus and Pleurotus ostreatus var. Florida, and Pleurotus djamor, where half of the treatments were scratched before the first and second flushes, while the rest were only scratched before the second flush. Yield (%), biological efficiency (%), weight of mushroom (g) and number of mushrooms (uni) were evaluated. It was observed that scratching harmed the mushroom weight for P. ostreatus, where the treatment without scratching produced significantly higher values, in the first harvest flush. On the other hand, scratching favored yield and the number of mushrooms for P. djamor. When the species are compared, it is noted that P. ostreatus obtained a lower yield, which was also reflected in the biological efficiency. P. djamor stood out with a large number of mushrooms, statistically higher than the other species, on the other hand, producing mushrooms of low weight of mushroom. The use of the scratched technique is not recommended for the conditions used in the work, due to the increase in labor and loss of mushroom weight.
Keywords: cultivation technique; mycelium breaking; oyster mushroom; screening of mushroom quality; yield